Teoritisasi Komunikasi Dalam Tradisi Sosiokultural - Eko Nugroho (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2019)
ABSTRACT The Last Samurai is a Hollywood production film made by Edward Zwick (2003) which won 4 (four) Oscars for several categories at the 2004 Academy Award. In this film, we can see Katsumoto and Algreen at first debating or disagreeing about ways the customs. Socioculturally, there are keywords that can be seen in the film's story, namely